Treatment of Scrap Tire for Rubber and Carbon Black Recovery - Alaa Sultan Abdulrahman; Fawzi Habeeb Jabrail (Recycling, 2022)
In this study, a chemical dissolution treatment was used to recover rubber and carbon black (CB) from truck tire scrap, with gas oil acting as the solvent and 4-Hydroxy-TEMPO acting as the catalyst for the chemical reactions. Montmorillonite clay was used to separate the rubber solution from the CB and the other non-dissolved tire additives. The recovered rubber and CB were characterized together with the original scrap tire sample by XRD, SEM, BET and thermal analysis, as well as FTIR and 1H NMR spectral analyses. Characterization of the chemical structure of the recovered rubber showed that the main functional groups of styrene−butadiene rubber blend with natural rubber. The thermal behavior and crystalline structure of the recovered rubber, as well as its morphological images, showed that the properties of the rubber sample were acceptable and similar to natural rubber. The recovered CB characterizations showed that the sample after pyrolysis was a highly crystalline nanocomposite structure with a high specific surface area and scattered pores.